Robust augmented reality guidance with fluorescent markers in laparoscopic surgery - Stenau, Esther; Teber, Dogu; Simpfendörfer, Tobias; Kenngott, Hannes Götz; Maier-Hein, Lena (International journal of computer assisted radiology and surgery, 2016)
Laparoscopic interventions require the precise navigation of medical instruments through the patient’s body, while taking critical structures into account. Although numerous concepts have been proposed for displaying subsurface anatomical detail using augmented reality, clinical translation of these methods has suffered from a lack of robustness as well as from cumbersome integration into the clinical workflow. The purpose of this study was to investigate the feasibility of a new approach to intra-operative registration based on fluorescent markers.
Gesehen am 12.08.2020